Detection and Resistance of Staphylococcus aureus chiken meats to some antibiotics - Rastina Rastina; Mahdi Abrar; Erina Erina; Winaruddin Winaruddin; Suryani Suryani (The Faculty of Veterinary Medicine of Syiah Kuala University, 2020)
Abstract